Simplifying
5g + h = g
Solving
5g + h = g
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '-1g' to each side of the equation.
5g + -1g + h = g + -1g
Combine like terms: 5g + -1g = 4g
4g + h = g + -1g
Combine like terms: g + -1g = 0
4g + h = 0
Add '-1h' to each side of the equation.
4g + h + -1h = 0 + -1h
Combine like terms: h + -1h = 0
4g + 0 = 0 + -1h
4g = 0 + -1h
Remove the zero:
4g = -1h
Divide each side by '4'.
g = -0.25h
Simplifying
g = -0.25h